A multisensory mindfulness experience: exploring the promotion of sensory awareness as a mindfulness practice - Finck, Carolyn; Avila, Alba; Jiménez-Leal, William; Botero, Juan Pablo; Shambo, Daniel; Hernandez, Susana; Reinoso-Carvalho, Felipe; Andonova, Veneta (Frontiers in Psychology, 2023)
Objectives: In this preliminary and multidisciplinary exploratory study, we assess whether mindfulness practice could be enhanced through a multisensory experience design that mimics the "beginner's mind", relying on sensory awareness and biofeedback processes as participants interact with the experience. Methods: We piloted and designed two conditions, being a) a guided mindfulness practice based on the senses as an anchor to the present moment, using audio instruction only; and b) an experience of mindfulness practice with successive sensory stimulation (olfactory, audio, visual stimulation) followed by an interactive experience with biofeedback that provides a visual representation of the person's heartbeat in real-time. For each of the conditions we assessed anxiety (state and trait), as well as other psychological variables pre-and post-experience. Additionally, we measured the heart rate variability (HRV) at baseline, during each stage of the experience as well as post intervention. Results: We collected valid data for a total of 67 individuals. Both groups were similar regarding mean age, sex, and occupation and had similar prior experience with mindfulness. There were no significant differences regarding prior state or trait anxiety between the groups. Analysis of the physiological variables showed that for both groups there was an increase in the parasympathetic activity after the multisensory experience, with small differences in the conditions of stimulation. We did not observe significant differences between the pre and post measures for state of anxiety. Conclusions: Participants in both conditions could effectively connect with the experience, while achieving a physiological response different from their baseline state. The acceptance of the designed stimuli was very high, although more research is still needed to uncover its full potential. In sum, the design of multisensory experiences using technology to create an interactive connection with the sensory stimulus, is a promising field in mindfulness and especially in practices involving sensory awareness through the monitoring of parasympathetic activity as an inference indicator of the present-moment connection.